Minat Baca Siswa Melalui Gerakan Literasi Sekolah (GLS) di Kelas V Sekolah Dasar Negeri 1 Bakam - Sunita; Yuanita; Gatot Afrianto (Universitas Muhammadiyah Bangka Belitung, 2025)
The School Literacy Movement (GLS) is one of the initiatives aimed at fostering students' interest in reading; however, its success requires strong support and commitment from the school environment. This study aims to analyze the level of reading interest among fifth-grade students at State Elementary School 1 Bakam through the implementation of the School Literacy Movement, which includes a 15-minute reading activity before lessons begin and the establishment of reading corners. A descriptive qualitative method was employed to analyze and present the research findings. Data were collected through interviews, questionnaires, observations, and documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, presentation, verification, and conclusion drawing. The results show that students are interested in reading activities, as reflected in their responses to the 15-minute pre-lesson reading activity (91% strongly agreed, 9% agreed) and the reading corner initiative (89% strongly agreed, 11% agreed). Based on these findings, the School Literacy Movement positively impacts students' reading interests, supported by the consistent commitment of homeroom teachers in implementing the program.